2016
DOI: 10.1259/bjrcr.20150497
|View full text |Cite
|
Sign up to set email alerts
|

Primary phosphaturic mesenchymal tumour of the lumbar spine: utility of 68Ga-DOTATOC PET/CT findings

Abstract: Primary phosphaturic mesenchymal tumours (PMTs) frequently occur in the soft tissue or bone, but rarely in the spine. The majority of patients experience long-term ostalgia and recurrent fractures. Detection of PMT can be challenging, but the clinical symptoms dramatically improve after removal of the tumour.Wepresent a case of primary PMT in the lumbar spine. CT scan showed a low-density tumour with a well-defined sclerotic margin in the L5 vertebra. MRI revealed a hypointense tumour on T2 weighted imaging an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Clinically, PMT generally presents as a solitary lesion in various areas of bone, such as femur [ 25 , 26 ], tibia [ 27 , 28 ], cervical vertebra [ 29 , 30 ], lumbar vertebra [ 31 ], sacrum [ 32 ], phalanx [ 33 ], metacarpal [ 34 ], maxilla [ 20 ], and mandible [ 35 ]. Notably, Nathan et al reported a patient with the first PMT in the tibia, and the second in the maxillary sinus occurring 2 years later [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, PMT generally presents as a solitary lesion in various areas of bone, such as femur [ 25 , 26 ], tibia [ 27 , 28 ], cervical vertebra [ 29 , 30 ], lumbar vertebra [ 31 ], sacrum [ 32 ], phalanx [ 33 ], metacarpal [ 34 ], maxilla [ 20 ], and mandible [ 35 ]. Notably, Nathan et al reported a patient with the first PMT in the tibia, and the second in the maxillary sinus occurring 2 years later [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small studies by Agrawal et al [ 46 ] and Jadhav et al [ 47 ] also reported higher sensitivity and specificity for SSTR tracers compared with [ 18 F]FDG. Multiple other case and small studies summarized in Table 2 report localization of culprit lesions in patients with TIO using SSTR tracers [ 14 , 38 , 39 , 40 , 41 , 42 , 44 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. An example showing culprit lesions identified in 3 patients using [ 68 Ga]Ga-DOTATATE PET-CT from a small study by John et al [ 38 ] is shown in Figure 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells stimulate upregulation of fibroblast growth factor 23 (FGF-23), preventing formation of 1, 25-dihydroxyvitamin D3 (calcitriol), which inhibits reabsorption of phosphate in the kidneys [ 5 , 7 , 9 , 10 ]. PMTs have been reported in bone and soft tissue, including the thigh, foot, hip, head, neck, and spine [ 1 , 2 , 3 , 4 , 5 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%